2023
DOI: 10.2147/ijn.s440034
|View full text |Cite
|
Sign up to set email alerts
|

Microcurrent Cloth-Assisted Transdermal Penetration and Follicular Ducts Escape of Curcumin-Loaded Micelles for Enhanced Wound Healing

Pei-Chi Lee,
Cun-Zhao Li,
Chun-Te Lu
et al.

Abstract: Purpose Larger nanoparticles of bioactive compounds deposit high concentrations in follicular ducts after skin penetration. In this study, we investigated the effects of microcurrent cloth on the skin penetration and translocation of large nanoparticle applied for wound repair applications. Methods A self-assembly of curcumin-loaded micelles (CMs) was prepared to improve the water solubility and transdermal efficiency of curcumin. Microcurrent cloth (M) was produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
(107 reference statements)
1
2
0
Order By: Relevance
“…The Zn particles did not fully cover the underlying silk fibers (Figure 2C,D). Furthermore, the SEM images of the Zn/Ag printed pattern vividly demonstrated that the metallic particles formed a layer over the underlying silk fibers, and the energy-dispersive X-ray spectroscopy (EDX) analysis, as outlined in our previous study [18], confirmed the presence of Ag and Zn on the Zn/Ag electrode-printed patches. SEM should be used to characterize the microstructure of the iontophoretic patches, as this information provides insight into the electrochemical properties of the electrodes and the overall performance of the patches.…”
Section: Microstructure Of Iontophoretic Patch (Microstructure and Po...supporting
confidence: 64%
See 2 more Smart Citations
“…The Zn particles did not fully cover the underlying silk fibers (Figure 2C,D). Furthermore, the SEM images of the Zn/Ag printed pattern vividly demonstrated that the metallic particles formed a layer over the underlying silk fibers, and the energy-dispersive X-ray spectroscopy (EDX) analysis, as outlined in our previous study [18], confirmed the presence of Ag and Zn on the Zn/Ag electrode-printed patches. SEM should be used to characterize the microstructure of the iontophoretic patches, as this information provides insight into the electrochemical properties of the electrodes and the overall performance of the patches.…”
Section: Microstructure Of Iontophoretic Patch (Microstructure and Po...supporting
confidence: 64%
“…Silver (Ag) ink (Creative Materials Inc., Ayer, MA, USA) or carbon (C) ink (Creative Materials Inc., Ayer, MA, USA) were used to print the cathode, and an in-house zinc ink, consisting of Zn particles (<10 µm; Sigma Aldrich, St. Louis, MO, USA), was used for the anode. Zn/Ag ink and Zn/C ink were printed on a silk substrate to prepare the Zn/Ag or the Zn/C-electrode-printed patches, manufactured by xTrans Creative Inc (Taipei, Taiwan) [18]. Polyvinyl alcohol (PVA; Sigma Aldrich), a biocompatible binder, was used to hold the Zn particles in the ink and effectively adhere the particles to the supporting fabric during the printing and curing [19][20][21].…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation